2019
DOI: 10.1182/blood-2019-129198
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of CD81 By Epigenetic Drug Combination Sensitizes Acute Lymphoblastic Leukemia Via Decreased BTK Signaling

Abstract: Background We previously discovered that the epigenetic drug combination - azacitidine (aza, DNMTi) and panobinostat (pano, HDACi) can sensitize ALL cells to chemotherapy (Quagliano et al., Leuk Res, 44:101, 2017). This sensitization occurred through a decrease in cellular adhesion and a modulation of the cell surface expression of the tetraspanin protein CD81 (Quagliano et al., Blood, 132:3957, 2018). This study aims to elucidate the molecular mechanism by which CD81 surface modulation by pre-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This resulted in the depletion of Bruton tyrosine kinase signaling and a sensitization to chemotherapy. 42 This highlights the secondary effect that TSPANs can have on intracellular signaling by controlling the expression of specific cell surface proteins.…”
Section: Tspans and Their Role In Bmc In Hematologic Malignanciesmentioning
confidence: 99%
“…This resulted in the depletion of Bruton tyrosine kinase signaling and a sensitization to chemotherapy. 42 This highlights the secondary effect that TSPANs can have on intracellular signaling by controlling the expression of specific cell surface proteins.…”
Section: Tspans and Their Role In Bmc In Hematologic Malignanciesmentioning
confidence: 99%
“…Additionally, a study of the use of azacitidine and panobinostat in B-ALL identified that following treatment in mice; leukemic cells were mobilized from the bone marrow into the peripheral blood. This mobilization was responsible for the improved efficacy of subsequent chemotherapy treatment, thus suggesting that staggering the treatments had a significant effect ( 170 ). More study on this effect as well as its potential in other cancer subtypes must be performed to exploit the efficacy of epigenetic treatments.…”
Section: Need For Clinical Trialsmentioning
confidence: 99%